2018
DOI: 10.1029/2017jd027292
|View full text |Cite
|
Sign up to set email alerts
|

Hygroscopicity of Organic Aerosols and Their Contributions to CCN Concentrations Over a Midlatitude Forest in Japan

Abstract: The formation of biogenic secondary organic aerosols (BSOAs) in forest environments is potentially important to cloud formation via changes of the cloud condensation nuclei (CCN) activity of aerosols. In this study, the CCN activation of submicrometer aerosols and their chemical compositions and size distributions were measured at a midlatitude forest site in Japan during the summer of 2014 to assess the hygroscopicity of the organic aerosols and their contributions to the local CCN concentrations. The mean nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 85 publications
(179 reference statements)
4
29
3
Order By: Relevance
“…Previous observational studies at the site indicated that BSOA formation was intensive and that aging occurred after formation (Han et al, 2014;Deng et al, 2018). It was also observed that org was time and size dependent and that the contribution of OA and BSOA to CCN number concentrations could be substantial (Deng et al, 2018). This work is an extension of previous studies on the hygroscopicity 5 and CCN activity of aerosols, and the contributions of OA and BSOA to the CCN concentration, in the same forest (Kawana et al, 2017;Deng et al, 2018).…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…Previous observational studies at the site indicated that BSOA formation was intensive and that aging occurred after formation (Han et al, 2014;Deng et al, 2018). It was also observed that org was time and size dependent and that the contribution of OA and BSOA to CCN number concentrations could be substantial (Deng et al, 2018). This work is an extension of previous studies on the hygroscopicity 5 and CCN activity of aerosols, and the contributions of OA and BSOA to the CCN concentration, in the same forest (Kawana et al, 2017;Deng et al, 2018).…”
Section: Introductionsupporting
confidence: 60%
“…Furthermore, the influence of these variations on the fractional contribution of OA and BSOA to the CCN concentration was assessed. Previous observational studies at the site indicated that BSOA formation was intensive and that aging occurred after formation (Han et al, 2014;Deng et al, 2018). It was also observed that org was time and size dependent and that the contribution of OA and BSOA to CCN number concentrations could be substantial (Deng et al, 2018).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations